First evidence of treatment efficacy in metastatic carcinoma of the parotid gland with BRD4/NUT translocation. (3rd May 2016) - Vulsteke, Christof; Lurquin, Eveline; Debiec-Rychter, Maria; Gheysens, Olivier; Nuyts, Sandra; Schoenaers, Joseph; Politis, Constantinus; Mebis, Jeroen; Hauben, Esther; Clement, Paul M.
Abstract : Background: Nuclear protein in testis (NUT) midline carcinomas (NMC) are characterized by rearrangements of the gene NUT. In the majority of NMCs, a translocation t(15;19), resulting in a BRD4/NUT fusion gene, is present. Nuclear protein in testis midline carcinomas is a rare, but probably underdiagnosed entity due to misdiagnosis. Most cases have been reported in the mediastinum and upper aero-digestive tract. The clinical course of a NMC is extremely aggressive, in spite of intensive chemotherapy and radiotherapy, with an average survival < 1 year. Methods and results: A 32-year-old man presented with a pre-auricular swelling on the left side. After partial parotidectomy, the diagnosis of a NMC was made based on the presence of t(15;19)(q14;p13.1) and BRD4/NUT fusion gene demonstrated by fluorescence in situ hybridization (FISH). During postoperative radiotherapy, the patient developed bone metastases for which chemotherapy consisting of cisplatine, doxorubicine and ifosfamide (PAI) was initiated with remarkable clinical and radiological improvement. Nevertheless, the response was not durable. Conclusion: This case illustrates that responses to chemotherapy in the palliative treatment of a t(15;19)-translocated salivary gland carcinoma are possible but not durable.